HALAL SEBAGAI BAHASA IDENTITAS PRODUK KECANTIKAN WARDAH: ANALISIS WACANA KRITIS - Kuspita Sari; Bambang Wibisono; Edy Hariyadi; Akhmad Sofyan; Didik Suharijadi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
In Indonesia, the trend of products using religious commodities filled the economic market, which used "halal" diction. This study aims to answer several questions. Firstly how is the halal commodification process produced related to Wardah products? Second, how is the halal commodification process produced related to Wardah advertisements? The last is about the halal commodification process in which discourse and a "power" battle space occur. Systematization reproduced the specific knowledge. In contrast, variants are presented in specific ways. The research approach used is descriptive qualitative research. Data collection activities were carried out using the listening method and recording techniques to transcribe the data obtained. The data analysis process is carried out using the discourse theory proposed by Michel Foucault, using the genealogical method. The study results indicate that in the process of producing halal commodification related to halal products, all discourses that move in the Wardah production area are opposed to everything outside of Wardah. Besides, the openness of the power system process shows that these relations do not always dominate each other but instead play a role in strengthening the power of the halal products produced by Wardah. The results showed that when halal advertisements produced by Wardah were distributed to consumers (the public), they experienced several responses. Some people support halal advertisements, people reject halal advertisements, and neutral society towards halal advertising. This community response becomes data that is processed, selected, and sorted for reconstruction, intending to strengthen further the existence of Wardah formed by halal advertising. The relationship between Wardah, which produces the halal advertisements with other subjects outside, is interpreted as a space for the process of power to take place.